MENINGKATKAN KEMAMPUAN GURU MENGORKESTRASI PEMBELAJARAN MeNaRIK MELALUI KEGIATAN FIG - Siregar, Salamat (STKIP Pesisir Selatan, 2022)
The massive expansion of Covid-19 to all aspects of life has forced mankind to form a new order that we commonly call the new normal. One of the sectors of life that suffers the most is the education sector, namely the occurrence of learning loss, which is a condition of loss of effective learning opportunities for students and a decrease in mastery of competencies. Ideas that are worthy of being used as alternative solutions to overcome learning problems during the COVID-19 pandemic are through school policies that favor students, that is